Elective caesarean section after 39 weeks gestation and the influence on neonatal morbidity: Does a strict policy really help? Elektivni carski rezi po 39. tednu nosečnosti in njihov vpliv na neonatalno obolevnost: Ali stroga pravila resnično pomagajo? - Mujezinović, Faris (Acta Medico-Biotechnica, 2021)
Purpose: The aim of the current study was to determine if the decision to strictly follow clinical guidelines recommending elective caesarean section at or after 39 weeks gestation (late– term) in an effort to reduce respiratory disorders in term neonates influence the incidence of early–term elective caesarean sections and the rate of neonatal respiratory disorders. Methods: Hospital records pertaining to elective caesarean section after 37 weeks gestation from 1 January 2007 to 31 December 2016 were analyzed. Two subgroups were established (“before” and “after”). The rate of elective caesarean section before 39 weeks gestation, the rate of neonatal respiratory disorders, and admissions to the neonatal intensive care unit were compared between the subgroups. Results: A total of 1881 elective caesarean sections were performed from 37 weeks gestation (1.083 [57.6%] in the before sub–group and 798 [42.4%] in the after sub– group). In the after sub–group there was a 9.8% reduction of procedures performed before 39 weeks gestation. Of the newborns, 1.59% had various respiratory problems (2.3% and 1.00% in the before and after sub–groups, respectively; p = 0.08). Six of 30 (20.0%) newborns were transferred to the neonatal intensive unit (4/22 [18.2%] and 2/8 [25.0%] in the before and after sub–groups, respectively). Conclusion: The policy reduced the rate of elective caesarean sections before 39 weeks gestation and the rate of neonatal respiratory disorders, even though the incidence of these disorders was rather low, even before the new policy.